KEPENTINGAN IRAN MELAKUKAN INTERVENSI TERHADAP KONFLIK INTERNAL YAMAN TAHUN 2014-2015 - Charin, Rizky Octa Putri; ", M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research explaining about Iran's interests to intervene by providing various forms of assistance to Shiite Houthi in dispute with the government and several other separatist groups in Yemen. Iran has given assistance from the 2005, but such aid increases the amount in the range of 2014 to 2015. At the end of 2014, the Shiite Houthi had secured several provinces in Yemen and the Yemeni capital, Sana'a, Shiite Houthi movement continued until the 2015 coup against the Shiite Houthi successful Yemeni presidential palace and become temporary ruler of Yemen. Post-coup happens, Iran increasingly overtly give political support and economic aid to the new government under the rule of the Shiite Houthi. This research is conducted by using neorealism perspective of international relations and supported by offensive realist theory. Formulation of facts, data, arguments, theoretical framework in this study using a qualitative description. This research has formulated answer-hypothesis which revealed the fact their interests ideological-political expansion of Iran for his actions intervening in Yemen's internal conflict. The interests of the ideological-political expansion of Iran is; Imami Shi'a ideology deployment in Yemen, the expansion of Iranian hegemony in the Middle East and the strategic value of the Strait of Bab el-Mandeb which is the fourth busiest shipping lanes in the world. This answer is based on the fact of the help given Iran to the Shiite Houthi such aid military weapons, military training aid and assistance by the national army, the Republican Guard of Iran and political support and economic aid to the new government of Yemen under the control of Shiite Houthi.Keywords: Iran, Yemen, Shiite Houthi, Intervention, Internal conflict, Coup, Government, Interest, Ideological-political